The Correlation between Students Perception about School Garden with the Attitude of School Environmental Management - Prastiwi, Lenny; Sigit, Diana Vivanti; Sedayu, Agung (Biosfer: Jurnal Pendidikan Biologi, 2015)
School garden is one of learning sources to introduce students with environmental education. Environmental education through school garden can form a student’s perception that helps to develop a good atittude of school environmental management. The aim of this study was to find out the correlation between student’s perception about school garden with the attitude of school environmental management. This study was conducted in May 2015 at SMAN 4 Tangerang and SMAN 5 Tangerang. This study used quantitative method through correlational studies. Sampling was done by simple random sampling used 214 students of class XI who had been using school garden as a learning sources. The analysis prerequisite test results are normally distributed and homogeneous data. The regression models was Ŷ = 19.41 + 0,672X, and the correlation coefficient was 0.715 which means there was positive correlation between student’s perception about the school garden with the attitude of school environmental management. The coefficient of determination was 51.1%. It can be interpreted that student’s perception about school garden contributed 51.1% to the attitude of school environmental management.